Extraction and partial purification of Aspergillus flavus cell wall associated saponin hydrolase - Amin, Hala A.; Ahmed, Faten M.; Awad, Hanem M.; Mohamed, Sayeda S.; Shokeer, Abeer (Acta Biologica Szegediensis, 2017)
In spite of the importance of saponin hydrolase (SH) enzyme, in the production of biologically active compounds from natural saponins, it is surprising that many aspects of its nature are unknown. The results of the present work revealed that Aspergillus flavus was capable of expressing three SH forms; extracellular, intracellular and cell wall-bound forms. SH cell bound enzyme constituted to more than 75% of the total enzymatic activity in the production medium. The sequential extraction process of SH cell bound enzyme revealed that 47.5% of SH was cytosolic and the rest (52.5%) was associated with the cell wall. The highest SH extraction yield was achieved when 0.25 M Tris-HCl lysis buffer supplemented with 1% Triton X-100 for 24 h at 4-25 °C and pH 8 were applied. Under these optimized conditions, A. flavus SH yield increased from 23.6 to 85.83%. The partial purification was achieved by applying successively acetone precipitation, lyophilization, dialysis, and anion exchange chromatography on Fractogel EMD DEAE-650S to the extract. The specific activity of the enzyme extract was 0.27 U/mg after 75% acetone fractionation, while that after anion exchange chromatography was 0.65 U/mg protein. The final enzyme preparation was 7.3-fold purer than the crude extract.